Le Deuil d'un pays imaginé : Rêves, luttes et déroute du Canada français, Les rapports entre le Quebec et la francophonie canadienne (1867-1975) - Martel, Marcel (Collection Amérique française., 1997)
Since 1960, relations between Quebec and the Canadian Francophonie have not ceased to crumble. In fact, the Quiet Revolution brought in its wake a renewal of the identity discourse in French Canada. Marcel Martel gives us here a fascinating historical and political study of the relations between these communities from 1867 to 1975, the year preceding the election of the Parti Québécois. Studying some of the main catalysts such as the Order of Jacques-Cartier, the Council of French Life in America, the Canadian Association of French Education in Ontario, the Second Congress of the French Language and the Estates General of French Canada, it shows how the project of the French Canadian nation has changed over the years. It also identifies the causes that have led Francophone minority communities to be wary of intervention by the Quebec state.